The Role of Madrasah Principal in Developing the Innovation of The Tahfidzul Qur'an Juz 30 Program - Pamuji, Slamet; Nurfuadi (Universitas Pendidikan Ganesha, 2022)
Schools principals as leaders have the task of realizing the vision and also developing innovation in the implementation process. Quality educational institutions can be realized if they are supported by leaders who understand leadership and quality management. Tahfidzul Qur'an Jus 30 is a very important component in determining the competence of graduates. This study aims to analysis the principal's leadership innovation in developing the tahfidzul Qur'an Jus 30 program and the factors that support and hinder it. This study uses a qualitative approach. Methods of data collection is done through observation, interviews, and documentation. While the data validity technique uses triangulation and source methods. Data analysis techniques using interactive models consist of data collection, data reduction, data presentation, and leveraging. The results of this study indicate that the principal works as an innovator and also a very good supervisor. This can be seen from how the principal in making innovations and supervising the tahfidzul Qur'an team in the tahfidzul Qur'an Jus 30 learning activities, as a result, students and students managed to achieve the competencies that had been determined and even surpassed it.